Dynamic web-based driver task assignment calendar system project - Lee Lay, Khoon (2013)
Dynamic Web-Based Driver Task Assignment Calendar System (DCS) is a system specially design for Setiausaha Kerajaan Pahang (SUK) to help staff manages booking for customer and driver assignment task. Due to old traditional paper booking vehicle and paper assign driver’s task method, SUK decided to have a proper system to manage all the stuffs, and bookings. This system is developed by using open source tool which is notepad, XAMPP and MySQL. Besides that DCS also implement Rapid Application Development (RAD) methodology as a guideline to keep track the entire tasks complete on time.